UNSIGNALIZED INTERSECTION EVALUATION USED KAJI SOFTWARE IN SLAMET RIADI STREET – KAPAL PINISI 7 STREET BONTANG - FUDIN, ALI (KURVA S JURNAL MAHASISWA, 2015)
The intersection between Slamet Riadi Street and Kapal Pinisi Street Bontang  is crossing with three arms unsignalized intersection . This unsignalized intersection near to Citra Mas Lok Tuan market that have high traffic volume with the condition of crossing without signal and market activities. Then many conflicts among vehicles because of the traffic passing through the intersection is free in all directions without any arrangement. This research has aimed to :Analyze unsignalized intersection traffic flow in slamet riadi street – kapal pinisi 7 street.Assess the performance unsignalized intersection in slamet riadi street – kapal pinisi 7 street.Acknowledge unsignalized intersection Level of Service/LOS in slamet riadi street – kapal pinisi 7 street.Predict unsignalized intersection Level of Service/LOS in the next five years.In this study, Kaji Software was implemented to do this unsignalized intersection evaluation. The result of the evaluation was :Unsignalized intersection traffic volume analysis based on Peak Hour survey data in slamet riadi street – kapal pinisi 7 street :Right turn from east arm                           : 2276 vehicles/hourLeft turn from west arm                           : 2070 vehicles/hourRight and left turn from north arm                       : 938 vehicles/hourThe performance calculation of unsignalized intersection  in slamet riadi street – kapal pinisi 7 street : capacity ( c ) : 4140 smp/hour, saturation degree (DS) :  0,605 < 0,85, minor intersection delay : 9,54 < ( 5,1 – 15,0), major intersection delay : 5,35 < ( 5,1 – 15,0 ).The result of unsignalized intersection Level of Service / LOS in slamet riadi street – kapal pinisi 7 street, Ratio v/c : 0,605, based on LOS table from Morlok I, chater II on table 2.10, the existing performance of unsignalized intersection  in slamet riadi street ( east and west ) – Kapal Pinisi 7 street, ratio v/c : 0,605 < 0,85 has level of service / LOS = C, where the traffic was stable, speed controlled by the traffic, and limited speed.The result of performance prediction and Level of Service / LOS for the next five years : Traffic Flow ( Q ) : 3700,79 smp/hour, Capacity ( C ) : 4104,00 smp/hour , saturation degree (DS) : 0,902, Level of Service / LOS, Ratio v/c : 0,902 > 0,85 and Level of Service / LOS E, where the traffic flow unstable